Is there a trade-off between inflation variability and output-gap variability in the EMU countries? - Philip Arestis; Kostas Mouratidis (Levy Economics Institute of Bard College, 2002)
This paper examines two issues. First, we compare, based on the ratio of output-gap variability to inflation variability, the monetary policy performance of eleven EMU countries for the whole period of the EMS. Second, we examine whether the introduction of an implicit inflation-targeting by the EMU member countries after the Maastricht Treaty changed the trade-off between inflation variability and output-gap variability. We employ a stochastic volatility model for the whole period of the EMS and for two sub-periods (i.e., before and after the Maastricht Treaty). We find that for the whole period the trade-off ratio varies among EMU countries, especially in the case where industrial production is utilized to construct the output-gap variable. The results also vary from the point of view of how the trade-off variabilities change for each country before and after the Maastricht Treaty. The implication of these findings is that asymmetries exist in the euro area as a result of either different monetary policy preferences or different economic structures among the EMU's member countries.
Keywords: 330